Surgical Experience of Neglected Lower Cervical Spine Fracture in Patient with Ankylosing Spondylitis - Jo, Dae-Jean (The Korean Neurosurgical Society, 2010)
The management of lower cervical fractures in patients with ankylosing spondylitis (AS) differs from normal cervical fractures. Patients with AS are highly susceptible to extensive neurologic injuries and spinal deformities after cervical fractures from even minor traumatic forces. These injuries are uniquely complex, require careful imaging assessment, and aggressive surgical management to optimize spinal stability and functional outcomes.